HUBUNGAN PENGETAHUAN GIZI, BODY IMAGE DAN KONSUMSI MAKANAN CEPAT SAJI DENGAN STATUS GIZI REMAJA PUTRI DI SMA KECAMATAN GRESIK - Zuratul Hasanah; Desty Muzarofatus Sholikhah; Dwi Novri Supriatiningrum (Universitas Muhammadiyah Gresik, 2022)
Adolescents were vulnerable to nutritional problems. Knowledge of nutrition, body image, and consumption of fast food are factors studied and analyzed for their significant level on the nutritional status of adolescents. The purpose of the study was analyzed the relationship between nutritional knowledge, body image, and consumption of fast food with the nutritional status of adolescent girls in Gresik District Senior High School. This type of research uses an analytical observational cross-sectional approach. In this study, the independent variables were knowledge of nutrition, body image, and consumption of fast food, while the dependent variable was nutritional status. The number of samples was as many as 124 respondents divided by each high school and each class. Data collection used questionnaires and anthropometric measurements. Data analysis used Spearman rank The results of the Spearman rank correlation test on the nutritional knowledge variable with nutritional status obtained P value = 0.660> 0.05. In the body image variable with nutritional status, the P value = 0.445>0.05. Then fast food consumption with nutritional status obtained P value = 0,568 > 0.05 In this study it can be concluded that the relationship between nutritional knowledge, body image, and fast food consumption with the nutritional status of adolescent girls in SMA District Gresik there is no significant relationship on nutritional status.